Sifat Mekanik Bata Ringan Geopolimer Berdasarkan Rasio Si/AL - Fasya Khoirianti Rafrita; Siti Nur Rahmah Anwar; B. Sri Umniati (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The use of fly ash or fly ash is still minimally applied in Indonesia. The percentage of fly ash utilization is only 10-12% with 73% on Java Island and 27% on other islands, so there will be an accumulation of fly ash of up to 10.4 million tons per year by 2027. Abundant fly ash can be utilized by making lightweight brick the main composition as a substitute for cement called geopolymer lightweight brick. The fly ash used is class F with mechanical testing based on the Si/Al ratio. This research was conducted to analyze the effect of activator content on mechanical testing consisting of compressive strength, split tensile strength, and modulus of rupture in order to obtain the mechanical properties of lightweight geopolymer bricks. The higher of the activator content, got the greater Si/Al ratio. The ratios at activator levels of 35, 40, and 45% were 2.42; 2.45; and 2.48. The difference between split tensile strength and compressive strength for 35% activator content is 6.45%; 40% is 5.94%; and 45% is 6.04% so it is included in high quality lightweight brick. The level of activator has a significant effect on the compressive strength, split tensile strength, and modulus of rupture. The lower Si/Al ratio results in higher and better compressive strength, split tensile strength, and modulus of rupture.